Peranan Pendidikan Multikultural Dalam Mengatasi Perilaku Bullying Di Smkn 1 Bantaeng - ahmad iqbal; Rezky Dwika Dana Putri; Putri Maulidyana Takbir; Hasruddin Nur (CV. ITTC INDONESIA, 2026)
This paper examines the strategic role of multicultural education in preventing bullying within the school environment. In the context of Indonesia as a diverse nation, multicultural education is positioned as an approach that fosters tolerance, empathy, justice, and respect for differences in culture, religion, ethnicity, and social status among students. The paper describes the concept, objectives, and urgency of multicultural education, and analyzes the forms, causes, and impacts of bullying, including physical, verbal, and psychological dimensions as well as the emergence of new perpetrators. Drawing on findings from studies conducted in primary schools, secondary schools, and Islamic boarding schools, it concludes that multicultural education is effective in reducing bullying by strengthening students’ civic disposition and inclusive social attitudes. Practical implementations discussed include curriculum integration, classroom and extracurricular programs, the establishment of anti-violence task forces, and school culture management that explicitly promotes anti-discrimination and anti-bullying values. Thus, multicultural education is presented as a key solution for shaping democratic, humanistic, and pluralistic student character in a plural society.